Dictionary of nature - Burnie, David (New York : DK, 1994)
Explains over two thousand key words in biology, biochemistry, botany, zoology, and anatomy in text and accompanying photographs.
What is nature? -- The science of life -- Cells -- The chemistry of life -- Inheritance & genetics -- Evolution -- Classifying living things -- Microorganisms -- Plants -- Fungi -- Plant biology -- Animals -- Animal biology -- Ecology -- Pioneers of biology.
"A DK Publishing book"--T.p. verso.
"DK concise encyclopedia"--Cover.
Cover title: Nature.
Includes index.
Elem. School Library Collection.
Wilson's Junior High School.
Keywords: Biology -- Miscellanea -- Juvenile literature; Nature -- Miscellanea -- Juvenile literature; Biology -- Miscellanea; Nature -- Miscellanea; Biology -- Miscellanea; Nature -- Miscellanea